Secondary ion mass spectrometry and resonant ionisation mass spectrometry studies of nickel contacts to silicon carbide. - Gareth David John (2004)
Time-of-flight secondary ion mass spectrometry (TOF-SIMS) and resonant ionisation mass spectrometry (RIMS) have been used to perform depth profile analyses on nickel (Ni) contacts to silicon carbide (SiC) to understand the interfacial properties. In particular, as-deposited Schottky contacts and high temperature annealed Ohmic contacts have been characterised. Previous literature had indicated that the chemistry of the interface controlled the electrical properties of the contact. Using the TOF-SIMS system, depth profiles have been performed with the standard duoplasmatron ion source and a newly introduced liquid metal ion gun. Sputtering conditions have been optimised enabling detailed depth profiling of Schottky and Ohmic samples. The data from these samples have indicated a distinct difference between the two contact types. Schottky samples have been shown to have an abrupt interface with any interfacial reaction appearing to be confined to the intimate interface. This region had no significant affect on ion yield. Conversely, the Ohmic samples exhibited an extended Si composition well into the Ni contact layer. Moreover, the ion yield varied substantially throughout the contact layer indicating matrix changes were present as a result of annealing to 1000&C. RIMS studied the variation of Ni atoms sputtered into the Ni ground state (a3F4) and first excited state (a3D3) to determine variation in chemical bonding as a function of depth through the contact. Using a defocused ion beam passing through an aperture, detailed depth profiles were obtained by using two-colour, two-step resonant ionisation scheme. Again, a significant variation exists between the RIMS signals from Ohmic and Schottky samples. The ratio of the excited state to ground state for Ni showed measurable variations indicative of multiple Ni-silicide phases. Models for these interfaces are proposed and support other studies performed on this material system. The success of these techniques is reviewed together with suggestions for experimental development.